The Use Of Ruqyah Quraniyah Therapy On The Effect Of Brain Waves Healing Tourette Syndrome Patients - Muhamad Ali Mustofa Kamal; Norita Md Norwawi; Nor Azila Noh; Robiatul Adawiyah Mohd @ Amat (Office of Religious Research and Development Ministry of Religious Affairs Semarang Indonesia, 2024)
Volume: 7 No: 2 (page: 231-248)